Key issues surrounding the management of non-communicable diseases including the management of diabetes post COVID-19 among developing countries with a specific focus on Bangladesh - Farhana Akter, Mainul Haque, Francis Kalemeera, Amanj Kurdi, Brian Godman (Journal of Applied Pharmaceutical Science, 2021)
This article does not have an abstract.
Keywords: Bangladesh, non-communicable diseases, diabetes, developing countries, COVID-19, health policies